Feasibility and impact study of a reward-based mobile application to improve adolescents' snacking habits - De Cock, Nathalie; Van Lippevelde, Wendy; Vangeel, Jolien; Notebaert, Melissa; Beullens, Kathleen; Huybregts, Lieven (Cambridge University Press, 2018)
Adolescents’ snacking habits are driven by both explicit reflective and implicit hedonic processes. Hedonic pathways and differences in sensitivity to food rewards in addition to reflective determinants should be considered. The present study evaluated the feasibility and impact of a mobile phone-delivered intervention, incorporating explicit reflective and implicit rewarding strategies, on adolescents’ snack intake.Adolescents (n 988; mean age 14·9 (sd 0·70) years, 59·4 % boys) completed a non-randomized clustered controlled trial. Adolescents (n 416) in the intervention schools (n 3) were provided with the intervention application for four weeks, while adolescents (n 572) in the control schools (n 3) followed the regular curriculum. Outcomes were differences in healthy snacking ratio and key determinants (awareness, intention, attitude, self-efficacy, habits and knowledge). Process evaluation data were collected via questionnaires and through log data of the app.No significant positive intervention effects on the healthy snack ratio (b=−3·52 (se 1·82), P>0·05) or targeted determinants were observed. Only 268 adolescents started using the app, of whom only fifty-five (20·5 %) still logged in after four weeks. Within the group of users, higher exposure to the app was not significantly associated with positive intervention effects. App satisfaction ratings were low in both high and low user groups. Moderation analyses revealed small positive intervention effects on the healthy snack ratio in high compared with low reward-sensitive boys (b=1·38 (se 0·59), P<0·05).The intervention was not able to improve adolescents’ snack choices, due to low reach and exposure. Future interventions should consider multicomponent interventions, teacher engagement, exhaustive participatory app content development and tailoring.